Uncover the Hidden Veils: Ophthalmoplegia in Breast Cancer: Poster Presentation - Case Report - Ophthalmologist - SITA PARAMITA AYUNINGTYAS; Syntia Nusanti; Salmarezka Dewiputri; M. Sidik (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Breast cancer can metastasize to many sites, but the orbit is an infrequent location. Orbital metastases represent 1%–13% of all orbital tumors, and the prognosis is rather poor. We reported a case of orbital metastases of breast cancer that led to findings of other sites involvement. Case Illustration : A 50-year-old female presented with an inward squint and double vision for 9 months before admission. Esotropia, abduction, and elevation deficits in both eyes were observed. The visual acuity of both eyes was 6/6. Orbital MRI revealed an intraconal irregular lesion near the medial rectus muscle, which was hyperintense with contrast and thickened medial rectus muscles of both eyes. She underwent lumpectomy of breast mass two years before admission and no follow-up after surgery. Histopathology showed invasive lobular carcinoma (ILC). We referred her to hematologist- oncologist to have workup on metastases and treatment. Lung and extensive bone metastases were discovered. She was diagnosed with metastatic breast cancer (stage IV) and treated with hormonal therapy and bisphosphonates. On 3-month follow-up, diplopia and gaze limitations persist. Discussion : Diplopia and motility disturbances are the most common symptoms and signs of orbital metastases, including extraocular muscle involvement. The horizontal rectus muscles are more commonly involved. ILC is more frequent histological subtype involving orbital as the orbits are rich in fat and may attract disseminated ILC cells. Conclusion : Ocular symptoms in patients with a history of breast cancer should always be investigated for metastatic disease. A multidisciplinary approach is mandatory to achieve the best therapeutic management and long-term surveillance.